Local Mitigation of Higher-Order Ionospheric Effects in DFMC SBAS and System Performance Evaluation - Somkit Sophan; Pornchai Supnithi; Lin M. M. Myint; Susumu Saito; Kornyanat Hozumi; Michi Nishioka (My University, 2023)
Abstract Dual-Frequency Muti-Constellation (DFMC) Satellite-Based Augmentation System (SBAS) is a new SBAS standard for aeronautical navigation systems. It supports aircraft navigation from the enroute to approach phases via the L1 and L5 frequencies (1575.42 and 1176.45 MHz). Although the ionosphere-free (IF) combination in the DFMC SBAS operation removes the first-order ionospheric delays in the pseudorange measurement, remaining terms including the satellite-clock offset errors and higher-order ionospheric (HOI) delays are still unaccounted for. The DFMC SBAS accuracy and integrity can be affected by the HOI effects, especially during severe ionospheric disturbances. In this work, we present the local DFMC SBAS corrections with and without the mitigation of HOI delays. We first estimate the HOI delay terms using the received pseudorange followed by separate satellite and receiver bias estimations based on the minimum sum-variance technique. The integrity terms can then be obtained. The performances of DFMC SBAS using GNSS data (GPS, Galileo, and QZSS) are evaluated using obtained GNSS data at stations in Thailand on the ionospheric quiet and disturbed days. The results show that with the HOI mitigation, the vertical positioning errors (VPE) on the quiet and disturbed days can be improved by 12% and 9%, whereas the vertical protection levels (VPL) are improved by 16% and 21%, respectively. In addition, we perform a preliminary assessment of DFMC SBAS based on the International Civil Aviation Organization (ICAO) requirements of two categories: LPV-200 and CAT-I showing promising results.
Keywords: GNSS augmentation; Pseudorange; Galileo (satellite navigation); Quasi-Zenith Satellite System; GNSS positioning and interference